Tax policy assessment in Slovenia: Case of interest tax shield - Tatjana Jovanović; Maja Klun (DANUBE: Law, Economics and Social Issues Review, 2017)
The tax policy assessment is an indispensable strategy within any modern country's system of governance. There are several types of "impact assessments", with RIA as one of the most commonly used. This tool is used to measure and analyse the benefits, costs and effects of a new or existing legal regime, which can be carried out by collecting and analysing empirical data in the context of a broader decision-making framework. The main objective of the paper is to analyse which stage the Slovenian regulatory impact assessment is in, and whether this stage is sophisticated enough to provide for the essential verification of tax policy and specific instruments, focusing mainly on the case of interest tax shield issues. Methodologically, the paper is based on a systematic literature review, a survey for public consultations and statistical tools for calculating the differences in internal indebtedness in different observed periods. The results show that the Slovenian RIA is not sophisticated enough to evaluate complex tax instruments and policy. Nevertheless, tax policy decision-makers should reconsider the implementation of a thin capitalization rule (but also future tax policy instruments) focusing also on other, non-tax revenue, factors.
Keywords: 330; Regulatory Impact Assessment; Tax Policy; Thin Capitalisation; Multinational Companies